2020
DOI: 10.3892/mmr.2020.11535
|View full text |Cite
|
Sign up to set email alerts
|

Methylation status of CpG sites in the NOTCH4 promoter region regulates NOTCH4 expression in patients with tetralogy of Fallot

Abstract: Tetralogy of Fallot (ToF) is the most common form of cyanotic congenital heart disease (cHd). although a lower methylation level of whole genome has been demonstrated in ToF patients, little is known regarding the dna methylation changes in specific gene and its associations with TOF development. noTcH4 is a mediator of the notch signalling pathway that plays an important role in normal cardiac development. However, the role of epigenetic regulation of the NOTCH4 gene in the pathogenesis of ToF remains unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Aberrant methylation of promoter CpG islands is known to contribute to the phenotypic expression of CHDs, including TOF and VSD ( 3 ). Our previous studies identified that the altered expression of some genes involved in cardiac development, such as Notch4 and COUP transcription factor 2 in TOF, may be associated with the abnormal methylation of their promoters ( 26 , 27 ). In the current study, no significant difference was observed in the integral methylation level of DLK1 promoter between the patients with TOF and controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aberrant methylation of promoter CpG islands is known to contribute to the phenotypic expression of CHDs, including TOF and VSD ( 3 ). Our previous studies identified that the altered expression of some genes involved in cardiac development, such as Notch4 and COUP transcription factor 2 in TOF, may be associated with the abnormal methylation of their promoters ( 26 , 27 ). In the current study, no significant difference was observed in the integral methylation level of DLK1 promoter between the patients with TOF and controls.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, no significant difference was observed in the integral methylation level of DLK1 promoter between the patients with TOF and controls. However, previous studies have demonstrated that the methylation of certain CpG sites can affect gene expression ( 26 , 28 , 29 ). Therefore, the methylation status of each CpG site in the DLK1_R region was analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, we found DMR in ZFPM2 which is a gene highly related to Tetralogy of Fallot (TOF) in the DisGeNET database and ZFPM2 promoter hypermethylation has been found in TOF patients [ 67 ]. Moreover, HAND1 and NOTCH4 , in which we found DMR, display abnormal methylation patterns of their promoter regions in TOF patients [ 68 , 69 ]. Interestingly, TOF has been shown to be more prevalent in the ART-conceived population (adjusted OR 2.4, 95% CI 1.5–3.7) [ 70 ] even if an up-to-date meta-analysis did not find any increased risk of this congenital heart defect [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular abnormality is associated with a distinct gene signature in ECs (10,28). ETS1 could control the expression of several genes driving vascular abnormality, including MCAM (29), ANGPT2 (30), SOX4 (31), VEGFA/VEGFR2 (25,32), ITGA1 (33), NOTCH4 (34,35). However, the direct effects of ETS1 on function of tumor ECs remain poorly defined.…”
Section: Introductionmentioning
confidence: 99%